Why do wolves eat livestock? : - Imbert, Camille (2013)
Thanks to the protection by laws and the re-naturalization of habitat, the wolf (Canis lupus) is re-colonizing Europe from the resilient populations of Russia, Balcanic countries, Spain and Italy.In Italy, the major conservation issue is to limit the isolation of the populations, that suffers of a strong bottle neck effect and in this way assure the flow of individuals between the main populations of the Southern Apennines and Western Alps and create a link with Slovenian population.The wolves of Liguria plays thus a key role as it relay between the Apennines and the Alps sub-populations. However, they suffer of high poaching that limits the establishment of a stable population. Illegal killing is mainly due to conflicts with shepherds, derived by damages that wolves cause on livestock.In this study, we assessed wolf diet in Liguria by scat analysis , and the factors affecting it, by modeling the consumption of livestock using environmental features, wild ungulates diversity, husbandry characteristics and wolf occupancy (packs or dispersal individuals).Our results showed that wolves in Liguria consumed mainly wild ungulates (64.41%) and, to a lesser extent, livestock (26.28%). However, the diet of the wolf varies according to year and season, but also between packs and dispersal individuals.Our model reveals that presence of wild ungulates species (Roe deer), prevention on pastures and presence of stable packs, instead of single individuals, reduce livestock consumption. Thus, we suggest to promote wild ungulates expansion, the use of prevention tools in pastures and support wolf pack establishment (avoiding legal control and poaching), to develop a sustainable coexistence between wolf and human activities.